2007
DOI: 10.3340/jkns.2007.42.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hematoma Caused by Ruptured Traumatic Pseudoaneurysm of the Middle Meningeal Artery : A Case Report

Abstract: Hematomas caused by ruptured traumatic pseudoaneurysms of the middle meningeal artery (MMA) usually present with extradural hematomas, whereas intradural intraparenchymal hematomas are extremely rare. We report a case of traumatic pseudoaneurysm of the MMA giving rise to an intracerebral hematoma after head trauma. A 70-year-old man suffered a massive intracerebral temporoparietal hemorrhage after a head injury. CT angiogram of the brain revealed a large hematoma in the right middle cranial fossa extending to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 9 publications
(11 reference statements)
0
32
0
Order By: Relevance
“…It is sometimes associated with subdural hematomas or subarachnoid hemorrhage, 2) but the onset of intracerebral hemorrhage is extremely rare. 3) To our knowledge, nine patients have been reported [4][5][6][7][8][9][10][11] ( Table 1). Several studies indicated that temporal bone fracture crossing over the MMA was present in approximately 70%-90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is sometimes associated with subdural hematomas or subarachnoid hemorrhage, 2) but the onset of intracerebral hemorrhage is extremely rare. 3) To our knowledge, nine patients have been reported [4][5][6][7][8][9][10][11] ( Table 1). Several studies indicated that temporal bone fracture crossing over the MMA was present in approximately 70%-90%.…”
Section: Discussionmentioning
confidence: 99%
“…Bozzetto-Ambrosi et al 7) did not describe the severity of head trauma in a PMMA patient who developed intracerebral in the absence of fracture. As for mechanism of fracture-free PMMAs, Lim et al 5) speculated that closed head injury with traction injury of the vascular wall might be involved in the pathogenesis. Holland et al 13) assumed that the presence of a defect of the medial layer of the intracranial hemorrhage in the absence of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysms are less than 1% of all intracranial aneurysms and mostly associated with a history of trauma [4]. Pseudoaneurysms of the middle meningeal artery (MMA) are rare.…”
Section: Discussionmentioning
confidence: 99%
“…There are only six case reports of traumatic PMMA presenting with intracerebral bleed in the English literature. [1][2][3][4][5]7] In all of these patients, the clinical presentation was with an intracerebral bleed, and the pseudoaneurysm was only later detected by angiography. There has been no report of a giant pseudoaneurysm with an associated intracerebral bleed in literature.…”
Section: Traumatic Giant Pseudoaneurysm Of the Middle Meningeal Artermentioning
confidence: 96%
“…[1][2][3][4][5] Wang et al reported a patient who gradually developed an extradural giant PMMA over a period of 46 days and on the basis of their findings put forth four CT findings that may be useful for early diagnosis of such lesions; these are (1) basal skull fracture in the temporal region, (2) hypodense nodule within an acute hematoma, (3) hypodense nodule within an organized and encapsulated hematoma, and (4) strong and homogenous enhancement of the hypodense nodule within an organized and encapsulated hematoma. [6] Our patient had CT findings similar to those reported by Wang et al, [6] but differed from their description in that the bleed was intracerebral and the progression much more rapid (only 4 days).…”
Section: Traumatic Giant Pseudoaneurysm Of the Middle Meningeal Artermentioning
confidence: 98%